The astrophysical consequences of intervening galaxy gas on fast radio bursts. Issue 1 (2nd November 2017) - Prochaska, J. Xavier; Neeleman, Marcel
Abstract: We adopt and analyse results on the incidence and physical properties of damped Ly α systems (DLAs) to predict the astrophysical impact of gas in galaxies on observations of fast radio bursts (FRBs). Three DLA measures form the basis of this analysis: (i) the H i column density distribution, parametrized as a double power-law; (ii) the incidence of DLAs with redshift (derived here), _DLA(z)=A+B (z-C) with A=0.236_-0.021^+0.016, B=0.168_-0.017^+0.010 and C=2.87_-0.13^+0.17 ; and (iii) the electron density, parametrized as a log-normal deviate with mean 10 −2.6 cm −3 and dispersion 0.3 dex. Synthesizing these results, we estimate that the average rest-frame dispersion measure (DM) from the neutral medium of a single, intersecting galaxy is DM^NM_DLA=0.25 pc cm^-3 . Analysis of Al iii and C ii * absorption limits the putative warm ionized medium to contribute DM^WIM_DLA<20 pc cm^-3 . Given the low incidence of DLAs, we find that a population of FRBs at z = 2 will incur DM^NM_DLA(z_FRB=2)=0.01 pc cm^-3 on average, with a 99 per cent confidence level upper bound of 0.22 pc cm −3 . Assuming that turbulence of the interstellar medium (ISM) in external galaxies is qualitatively similar to our Galaxy, we estimate that the angular broadening of an FRB by intersecting galaxies is negligible (θscatt < 0.1 mas). The temporal broadening is also predicted to be small, τDLA ≈ 0.3 ms for a z = 1 galaxy intersecting a z = 2 FRB for an observing frequency of ν = 1 GHz. Even with ν = 600 MHz, the fraction of sightlines broadened beyond 25 ms is only approximately 0.1 per cent. We conclude that gas within the ISM of intervening galaxies has a minor effect on the detection of FRBs and their resultant DM distributions. Download the repository at https://github.com/FRBs/FRB to repeat and extend the calculations presented here.